(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Plastic waste generation and disposal contribute significantly to pollution and global warming. The properties and strength of bituminous mixtures are both enhanced by the inclusion of plastic detritus. Also, it will be a fix for other pavement issues including potholes, corrugation, ruts, and so forth. It was discovered that bitumen mixtures used in flexible pavements work well with plastic as a binder. By preventing cracks and rainwater infiltration, which would otherwise contribute to the development of potholes, this efficient method helps pavements tolerate greater temperatures. For India’s hot and extremely humid climate, where temperatures regularly exceed 50°C and torrential rains cause havoc and leave the majority of the roads with large potholes, plastic roads would be a godsend. Bitumen is used as a binder in the traditional road construction process. Such bitumen can be altered with leftover plastic bits to create a bitumen mix that can be applied as the top coat of flexible pavement. This modified bitumen made from discarded plastic exhibits enhanced adhesion, stability, density, and water resistance.